Development and validation of a nonaqueous titration with perchloric acid to determine sparfloxacin in tablets - Marona, HRN; Schapoval, EES (Elsevier B.V., 2001)
A simple, rapid and inexpensive method for the determination of sparfloxacin in tablets is described. The procedure is based on the use of volumetric dosage in a nonaqueous medium in glacial acetic acid with 0.1 M perchloric acid. The method validation yielded good results and included precision and accuracy. It was also found that the excipients in the commercial tablet preparation did not interfere with the assay. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: fluoroquinolone; nonaqueous titration; pharmaceutical analysis; sparfloxacin